Considerations teaching in gynecology - Chavarri, Manuel B. (1956)
The centenary we celebrate brings us here to offer a testimony of scientific diligence, the best tribute to the expectations placed on the Faculty members. However, in the individual case, there will be satisfech that aspect. My colleagues in the department of gynecology, chaired by Mr. Professor Dn. César Heraud have come to do so with greater success.